GRAMMATICAL ERRORS ANALYSIS ON EFL LEARNERS’ WRITING: : A case study at Junior High Islamic Boarding School in Jember - Tanzil Huda; Wakhyu Wuda (UIBU, 2019)
Writing is supposed to be a complicated language skill. There exists a lot of sub-skills should be learnt by EFL/ESL learners in order to write well such as vocabulary acquisition and grammatical mastery. In the process of writing, the learners should put ideas into phrases, clauses, and sentences by keeping the well-formedness of the structure. The learners should also be aware of that linguistic aspects when they are constructed a composition. Due to the complexity of writing skill, the learners potentially make error/s. The errors were potentially occured in Junior High Islamic Boarding School in Jember. The recent study was intended to investigate the dominant error/s made by the EFL learners at Junior High Islamic Boarding School in Jember. The study also tried to explore the factors cause those learners made the error/s. The study was a case one which employed the qualitative approach. This study revealed that the dominant error made by the students was misformation errors which were occured because of the interference of the learners’ mother tongue i.e., the learners still got confused to change the verb into past participle, as what it was called as intralanguage error in which it was taken place because inadequate knowledge how to use or to change verb. In addition, it was occured by some other factors such as environment, the process of teaching and learning including of learning style and feedback, the availability of learning source, and low motivation. In conlclusion, the dominant errors made by EFL learnes at Junior High Islamic Boarding School in Jember were omission of to be, omission of plural, omission of article, omission of preposition, simple addition, misformation, and misordering. In addition, the factors contributed to the errors were inadequacy of grammar competence, environment, learning feedback, and low learning motivation